The impact of a child bike seat and trailer on the objective overtaking behaviour of motorized vehicles passing cyclists. (November 2020) - Ampe, T.; de Geus, B.; Walker, I.; Serrien, B.; Truyen, B.; Durlet, H.; Meeusen, R.
Highlights: Drivers of motorized vehicles adapt their overtaking behaviour. Larger and therefore safer overtaking manoeuvres in cyclists transporting a child. In morning peak the child bike seat is the safest in terms of overtaking distance. More than a quarter of all overtaking manoeuvres was too close (<100cm). Abstract: Introduction: The lateral clearance distance of a motorized vehicle while overtaking a cyclist is a key indicator of safety. This lateral clearance distance has never been measured for cyclists transporting a child. Therefore the aim of this study was to investigate the behaviour of motorized vehicles in overtaking cyclists with and without a child on the same bicycle. Methods: The lateral clearance distance of the overtaking manoeuvres of motorized vehicles was measured using an instrumented bicycle when performing 19 cycling trips on one single road with two different types of cycling infrastructure (a bike lane and shared lane marking) in the Brussels Capital Region (Belgium). Mixed effect regression was used to examine the effect of cycling condition (cyclist without a child [control], cyclist with a child bike seat and cyclist with a child bike trailer) and secondary independent variables (i.e. cycling infrastructure, peak traffic hours and traffic density) on the lateral clearance distance. Results: The mean lateral clearance distance in 'cyclists without child' was significantly smaller (117.3 cm) than in 'cyclists with child' (128.8 cm) (95%CI [7.2;15.9]). Looking at 'morning peak traffic hours' (i.e. 7:00 to 9:00 a.m.) a cyclist with child bike seat was overtaken at greater lateral clearance distances than a cyclist with a child bike trailer or a cyclist without child ( p =0.041). Furthermore, the percentage of passing manoeuvres under 100 cm was significantly higher in 'cyclist without child' (35.3%) in comparison to 'cyclist with child bike seat' (21.8%) and 'cyclist with child bike trailer' (21.8%) (Chi2=29.19, p<0.001). No significant differences were found between a shared lane marking and bike lane. Conclusion: Drivers of motorized vehicles do adapt their overtaking manoeuvre when they overtake cyclists transporting a child, keeping greater and therefore safer lateral clearance distances. In morning peak traffic hours and/or crowded circumstances the child bike seat can be considered as the safest way to transport a child in terms of lateral clearance distance. In general, with 25.3% overtaking manoeuvres under 100cm, police should monitor compliance with the traffic rules with regard to cyclists, and motorists should be more aware of the overtaking traffic rules.